An integrated hybrid 3D bioprinting of heterogeneous and zone-specific construct resembling structural and biofunctional properties of osteochondral tissue - Yaxin Wang; Yanhao Hou; Cian Vyas; Boyang Huang; Paulo Bartolo (Materials Futures)
Extrusion-based 3D printing is extensively used to fabricate osteochondral (OC) constructs. However, significant challenges remain, particularly engineering constructs that can replicate the heterogeneity and structural organization of OC tissue and maintain a chondrogenic phenotype. Herein, this study introduces an integrated hybrid 3D bioprinting strategy, incorporating soft hydrogel bioinks and a bioceramic thermoplastic composite polymer, allowing the fabrication of a zone-specific construct analogous to OC tissue. The results show that the hybrid triphasic 3D bioprinted construct mimicking the full-thickness OC tissue displays a distinct layered structure with high precision and improved mechanical properties. The calcified layer fabricated by co-printing gelatin methacryloyl (GelMA) and polycaprolactone/tricalcium phosphate (PCL/TCP) enables the formation of a transition layer and provides strong bonding between the engineered PCL/TCP subchondral bone and the methacrylated methylcellulose (MCMA)/GelMA cartilage layer. The encapsulated human adipose-derived stem cells are found to be spatiotemporally released from the calcified cartilage layer and directionally attach to the subchondral bone layer of the construct. The MCMA/GelMA bioinks exhibit a stiffness and stress relaxation profile suitable for cartilage applications. Human chondrocytes (HCs) show enhanced cell viability and proliferation. Moreover, the HCs encapsulated within the MCMA/GelMA bioinks maintain their chondrogenic phenotype with high expression of collagen type II (Col2) and SOX9. At the liquid-matrix interface, they experience a loss of chondrogenic phenotype and potential chondrogenic-to-osteogenic trans-differentiation with the expression of the osteogenic marker collagen type I (Col1). This study provides a deep understanding and insightful view of chondrogenic behaviours responding to the microenvironment via extensive in-vitro studies and shed light on a promising approach for the future OC tissue regeneration.